Gender Equality and Human Rights - Sandra Fredman; Beth Goldblatt (United Nations, 2015)
There is a strong commitment to equality between women and men in international human rights law. The various actors within the treaty system who are tasked with elaborating on the meaning of human rights in international law have given close attention to gender equality. This work evaluates these elaborations against a conception of equality that is substantive. The achievement of substantive equality is understood here as having four dimensions: redressing disadvantage; countering stigma, prejudice, humiliation and violence; transforming social and institutional structures; and facilitating political participation and social inclusion. The publication suggests that there is a growing consensus at the international level on an understanding of substantive equality that reflects the four dimensions set out here. Making this understanding explicit will assist in addressing, through a range of means, the challenges of gendered inequality.